DETERMINASI OPINI AUDIT GOING CONCERN PERUSAHAAN DI SEKTOR MANUFAKTUR - Novietta, Liza; Ruzikha, Dinar (Jurnal Akuntansi & Keuangan, 2024)
This study aims to determine the effect of disclosure, audit tenure and opinion shopping on going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. In addition, this study also aims to determine whether company size is able to moderate the relationship between the independent variable and the dependent variable. This research is an associative study with a descriptive approach. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. The data used in this study is secondary data accessed through www.idx.co.id. Data analysis used logistic regression analysis for disclosure hypotheses, audit tenure, opinion shopping and company size. Then the residual analysis for disclosure, audit tenure and opinion shopping on going concern audit opinion with company size as a moderating variable. The results of this study indicate that disclosure, audit tenure and company size do not have a significant effect on going concern audit opinion. While opinion shopping has a positive and significant effect on going concern audit opinion. The moderating variable, namely company size, is unable to moderate disclosure, audit tenure and opinion shopping on going concern audit opinion.